Controlled overturning of unanchored rigid bodies. - Boroschek, Rubén (Earthquake engineering & structural dynamics.)
Typical small hospital and laboratory equipment and general supplies cannot be anchored to resist earthquake motions. In order to protect these non-structural components, a common procedure is to provide barriers to restrain overturning of objects on shelves and other furniture. In many cases this option is not available, especially for hospital equipment, because of other functional requirements. This work presents an alternative approach. The method proposed here does not avoid overturning, but controls the direction of overturning by providing an inclination to the support base so that the overturning occurs in a preferential direction towards a safe area. For example, objects on shelves, could overturn towards the inside or a wall, and equipment on tables could overturn away from the edge. In both cases this would not only reduce the damage to the particular items, but reduce the amount of debris on the floor. In order to determine the proper inclination of the base, specific rigid bodies are analytically evaluated for bi-directional excitation obtained from 314 earthquake records, in approximately 7500 cases. For each case, several inclination angles are evaluated. Finally, a parametric curve is adjusted to the data, given a relation between angle of inclination and percentage of controlled overturning cases. In all cases a 7° angle gives more than 98% confidence of controlled overturning. The design expressions were later compared with experimental results obtained on a six-degree-of-freedom shake table; confirming the analytical expressions.